2011
DOI: 10.1007/s11250-011-9894-1
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for Leptospirosis in goats in Uberlândia, Minas Gerais, Brazil

Abstract: The prevalence of Leptospirosis in goat herds of the State of Minas Gerais has seldom been studied. The present research had as its objectives: (1) investigate the seroprevalence of Leptospirosis in the county of Uberlândia, MG, (2) verify the Leptospirosis serovars, and (3) identify the risk factors associated with infection on the farms examined. Serum samples from 230 animals in 11 properties were tested using the microscopic agglutination test. An epidemiological examination furnished data for analysis reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
1
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 15 publications
6
16
1
12
Order By: Relevance
“…Hardjobovis and Autumnalis were the most frequent serovars of sheep and goats found in this study, a result that corroborates the findings of recent serological surveys conducted on small ruminants in Brazil (HERRMANN et al, 2004;LILENBAUM et al, 2007;ARAÚJO NETO et al, 2010;HIGINO et al, 2010;SALABERRY et al, 2011;CARVALHO et al, 2011;SANTOS et al, 2012;MARTINS et al, 2012;MORAES et al, 2012;ALVES et al, 2012;HIGINO et al, 2012;RIZZO et al, 2014). It was long believed that these animals acquired leptospirosis only by prior contact with other species (LEON-VIZCAINO et al, 1987), although the breeding of these species together with cattle breeding and the presence of rodents are important factors for the dissemination of the Hardjobovis and Autumnalis serovars, respectively (FAINE et al, 1999;SALABERRY et al, 2011;SEIXAS et al, 2011).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hardjobovis and Autumnalis were the most frequent serovars of sheep and goats found in this study, a result that corroborates the findings of recent serological surveys conducted on small ruminants in Brazil (HERRMANN et al, 2004;LILENBAUM et al, 2007;ARAÚJO NETO et al, 2010;HIGINO et al, 2010;SALABERRY et al, 2011;CARVALHO et al, 2011;SANTOS et al, 2012;MARTINS et al, 2012;MORAES et al, 2012;ALVES et al, 2012;HIGINO et al, 2012;RIZZO et al, 2014). It was long believed that these animals acquired leptospirosis only by prior contact with other species (LEON-VIZCAINO et al, 1987), although the breeding of these species together with cattle breeding and the presence of rodents are important factors for the dissemination of the Hardjobovis and Autumnalis serovars, respectively (FAINE et al, 1999;SALABERRY et al, 2011;SEIXAS et al, 2011).…”
Section: Resultssupporting
confidence: 92%
“…The low frequency of seropositives found in this study, compared with studies in other Brazilian regions, may be associated with a possible difference in susceptibility between the breeds of the animal species evaluated. Some studies showed that race is a risk factor for leptospirosis in small ruminants, in which a greater susceptibility to infection was observed among purebred animals compared with crossbred animals SANTOS et al, 2012). In the semi-arid region of Northeast Brazil, most of the sheep comprise of crossbred races (CEZAR et al, 2004), while the goats belong to native and indeterminate breeds with remarkable robustness (SILVA; ARAÚJO, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In small ruminants, breed has also been found to be a risk factor associated with leptospirosis (SALABERRY et al, 2011;SANTOS et al, 2012;SILVA et al, 2012). Therefore, the purpose of this study was to detect Leptospira spp.…”
Section: Microbiologymentioning
confidence: 99%
“…The presence of rodent infestations because of failures in health management, as proven by the substantial presence of serogroups associated with these reservoirs and with the consequent contamination of water sources, may explain the high rate of seropositive goat herds in Sergipe (90.24%), as also observed in Rio de Janeiro, Santa Catarina and municipality of Uberlândia, with rates of 100% (48/48), 90% (108/120) and 100% (11/11), respectively (LILENBAUM et al, 2007b;SANTOS et al, 2012;CORTIZO et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The most common serogroups in the Brazilian states were Icterohaemorrhagiae, which were positive in a sample from Ceará (FAVERO et al, 2002); Australis, Djasiman, Celledoni, Semaranga, and Sejroe, which were reported in the state of Paraíba (FAVERO et al, 2002;HIGINO et al, 2013;COSTA et al, 2016); Autumnalis, which were detected in Rio Grande do Norte; (ARAÚJO NETO et al, 2010); and Canicola and Autumnalis, which were reported in Pernambuco (CUNHA et al, 1999). Surveys were conducted in other Brazilian states, including Rio Grande do Sul, Santa Catarina, Rio de Janeiro, Espírito Santo, and Minas Gerais, and the infection rates were 2.4%-35.47% (FAVERO et al, 2002;SCHMIDT et al, 2002;LILENBAUM et al, 2007b;LILENBAUM et al, 2008;DOS SANTOS, et al, 2012;CORTIZO et al, 2015;TOPAZIO et al, 2015).…”
Section: Introductionmentioning
confidence: 99%